MODEL OF INTERNAL QUALITY ASSURANCE SYSTEM AT ISLAMIC BOARDING SCHOOLS AT RIYADLUSHARFI WALMANTIQ ISLAMIC BOARDING SCHOOL - Nurdiyanti, Yanti; Maulana, Acep Ridwan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The focus of this research aims to explore the model of the internal quality assurance system used in the Riyadlusharfi Walmantiq Islamic Boarding School as a perspective in running the pesantren's internal quality control system. This study used a qualitative approach with phenomenological types, data collection techniques were carried out through interviews, observation, and documentation. As for the analysis of research results using the Milles and Hubbarman technique and testing the validity of the data using the triangulation technique. Based on the results of the study it can be concluded that: the internal quality assurance system involves all elements of the pesantren namely kyai, ustadz and santri. And it has not been carried out through institutional formation in the form of community councils or other designations which are pesantren internal quality assurance institutions. The quality assurance cycle uses the PDCA cycle approach (plan, do, check, action). Where the long-term planning of Islamic boarding schools is implied in the vision of Islamic boarding schools which is actualized in the Islamic boarding school learning curriculum with the grouping at each level of the santri learning level which consists of the ibtida level, the mutawasit level and the mutaqodim level. With an evaluation system through the rote deposit method, imtihan and semester evaluations to be followed up which results in an increase in the learning level of the students. The educational model of the Riyadlussharfi Walmantiq Islamic Boarding School is integrated with formal education starting from PAUD, TK/RA, SMP/MTS, MA and Higher Education.